Assessment of Mycorrhizal Inoculant Effect on Sorghum Growth Performance and Soil Physical Properties in Andosol - Usama Yaseen; Jun Abe; Anne Nurbaity; Betty Natalie Fitriatin; Tualar Simarmata (Journal of the Indian Society of Soil Science, 2026)
Arbuscular mycorrhizal fungi (AMF) play a vital role in enhancing plant growth and soil health through symbiotic nutrient exchange. This study evaluated the effects of vesicular-arbuscular mycorrhizal (VAM) inoculation on the growth and physiological responses of Sorghum bicolor (L.) Moench under controlled greenhouse conditions at Tokai University, Japan, from August to September 2025. A completely randomized design with three treatments comprising commercial AMF inoculum, sterilized inoculum, and non-inoculated control was applied to plants grown in sterilized Andosol soil mixed with vermiculite. Growth parameters, including plant height, stem diameter, chlorophyll content, and soil electrical conductivity (EC) were measured weekly. Biomass traits and soil bulk density were assessed at harvest. Microscopic analysis confirmed AMF colonization through the presence of hyphae, spores, and vesicles. Data were analyzed using ANOVA and Tukey’s test at a 5% significance level. Results showed no significant differences in early vegetative traits; sterilized inoculum slightly enhanced plant height, reaching 61.5 cm, representing a 4.8% increase compared to the non-inoculated treatment (58.7 cm). Root biomass was also higher under sterilized inoculum, with fresh root weight reaching 12.1 g, approximately 27% greater than the non-inoculated treatment (9.5 g). Soil EC remained low and stable (0.062–0.086 dS m-1), while bulk density was significantly lower in the non-inoculated treatment (0.290 g cm-3) compared with inoculated treatments (0.650–0.652 g cm-3). These findings suggest that while physiological responses were initially uniform, specific treatments influenced vertical growth and soil structure, highlighting the potential of AMF in sustainable sorghum cultivation.